2013
DOI: 10.1002/mds.25380
|View full text |Cite
|
Sign up to set email alerts
|

A two‐year randomized controlled trial of progressive resistance exercise for Parkinson's disease

Abstract: Background The effects of progressive resistance exercise (PRE) on the motor signs of Parkinson’s disease have not been studied in controlled trials. Our aim was to compare 6, 12, 18, and 24 month outcomes of patients with Parkinson’s disease who received PRE to a stretching, balance, and strengthening exercise program. Methods We conducted a randomized controlled trial between September 2007 and July 2011. Pairs of patients, matched by sex and off-medication Unified Parkinson’s Disease Rating Scale, motor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
346
2
16

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 264 publications
(380 citation statements)
references
References 32 publications
16
346
2
16
Order By: Relevance
“…The decreased work and power generation observed in the early stages of PD suggest the need for early interventions that improve the muscular performance of these individuals. Recently, Corcos et al 32 observed improve in muscular strength and a 7.3 points decrease in UPDRS-III scores, which is a moderate clinically important change, after a 24-month progressive resistance exercise program (PRE). PRE progressively increased the resistance over time and each repetition lasted 6-9 seconds, that is, at slow speeds 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decreased work and power generation observed in the early stages of PD suggest the need for early interventions that improve the muscular performance of these individuals. Recently, Corcos et al 32 observed improve in muscular strength and a 7.3 points decrease in UPDRS-III scores, which is a moderate clinically important change, after a 24-month progressive resistance exercise program (PRE). PRE progressively increased the resistance over time and each repetition lasted 6-9 seconds, that is, at slow speeds 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Corcos et al 32 observed improve in muscular strength and a 7.3 points decrease in UPDRS-III scores, which is a moderate clinically important change, after a 24-month progressive resistance exercise program (PRE). PRE progressively increased the resistance over time and each repetition lasted 6-9 seconds, that is, at slow speeds 32 . The authors hypothesized that PRE may lead to experience-dependent plasticity in the basal ganglia and corticomotor pathways, which could contribute to improving signs and motor performance.…”
Section: Discussionmentioning
confidence: 99%
“…While specific elements of effective interventions have been described, there is no published consensus guideline regarding what type of intervention is the most beneficial form of regular physical activity in PD [21]. Resistance training has been shown to be beneficial in PD, and since there is no consensus regarding what type of intervention is most beneficial in PD, it serves as an appropriate comparison [22,23]. In this current study, we aimed to explore the feasibility of a yoga intervention in patients with PD both in a busy urban setting and a suburban setting, as well as to collect pilot data on preliminary efficacy compared to traditional resistance training to support a future larger scale efficacy study.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of motor and non-motor manifestations (e.g., depression, apathy and dementia) interferes with the individual's level of disability, and these factors negatively influence quality of life (QOL), which leads to isolation and low participation in social activities 6,7 . Distinct exercise modalities improve the symptoms of PD [8][9][10][11][12] . Exercise promotes plasticity of the central nervous system (CNS) 13 ; improves balance, gait, physical function and quality of life 8,9,14 , delays cognitive impairment 15,16 , dementia 17,18 , depression 19,20 ; and slows the progression of PD 21 .…”
Section: Introductionmentioning
confidence: 99%